Leadership, Work Competences, and Work Discipline in Lead the Employee Performance in Narcotics Unit of Surabaya Resort Police - Siskah Fernanda Novianti; Suyanto Suyanto (Maneggio, 2025)
Leadership, work competence, and work discipline are three main factors that play a major role in influencing employee performance in police institutions. If implemented properly, these three elements will create productive employees, have integrity, and are able to provide the best service in maintaining public security and order. This study aimed to review the influence of leadership, competence, and work discipline on employee performance in police institutions. This study used a quantitative approach, with data obtained from 82 respondents who are part of the Narcotics Unit of Surabaya Resort Police. Data were obtained through a survey mechanism with the help of an online questionnaire, and then analyzed using multiple linear regression analysis. The results of the research data processing showed that a) Leadership has a positive but insignificant influence on Employee Performance, with a t-count of 0.591; b) Work Competence has a positive and significant influence on Employee Performance, with a t-count of 2.901; c) Work Discipline has a positive and significant influence on Employee Performance, with a t-count of 3.456; d) Meanwhile, the results of the simultaneous test results showed that the F-count is 9.790, which shows that all independent variables consisting of Leadership, Work Competence, and Work Discipline simultaneously influence Employee Performance at the Narcotics Unit of Surabaya Resort Police.